UJI KOMPOSISI KIMIA KOMPOS Azolla mycrophylla DAN PUPUK ORGANIK CAIR (POC) Azolla mycrophylla - SRI UTAMI LESTARI; ENNY MUTRYARNY; NENG SUSI (Jurnal Ilmiah Pertanian, 2019)
ABSTRACT The aim of the study was to obtain the chemical composition of compost and POC Azolla mycrophylla. The study was conducted experimentally with the initial stages of composting and POC Azolla mycrophylla after which laboratory analysis of its chemical composition was carried out. Data analysis was carried out using qualitative descriptive analysis based on the results of laboratory tests on the chemical composition of Azolla-based compost. The results of the study concluded that the results of chemical analysis of compost and POC Azolla mycrophylla showed that the content of Azolla mycrophylla compost was higher than that of the Azolla mycrophylla POC. The results of the compost analysis of Azolla mycrophylla and Azolla mycrophylla POC have met the standards of organic fertilizer according to Minister of Agriculture No.28 of 2009.